SERVIS ATAS DALAM PERMAINAN BOLAVOLI (Studi Korelasi Kekuatan Lengan dan Koordinasi Mata-Tangan) - Kamadi, La (UNIVERSITAS NEGERI MAKASSAR, 2020)
This reseacsh aim at to determine the relationship between arm strength and eye-hand coordination with upper service ability in volleyball games. This research is a descriptive research. The population in this study were all students of SMPN 1 Ma'rang, Pangkep Regency with a total sample of 40 male students selected randomly. The data analysis technique used is the technique of correlation and regression analysis using the SPSS version 21 system at a significant level of 95% or Î± 0.05. Based on the results of data analysis, this study concluded that: 1) There was a significant relationship between arm strength and upper service ability in volleyball games; 2) There is a significant relationship between eye-hand coordination and upper service ability in volleyball play; 3) There is a significant correlation between arm strength and eye-hand coordination with upper service ability in volleyball.